Technology Acceptance Model (TAM) Dalam Evaluasi Pelaksanaan Rekam Medis Elektronik di Rumah Sakit - wulandari, fitria; Maureta, Rizkyana Putri; Agung, wardoyo (Politeknik Negeri Jember, 2025)
Hospital X in Semarang City has transitioned from paper-based medical records to electronic medical records (EMRs) in its outpatient unit. However, the implementation has faced obstacles, particularly frequent system response failures (freezing), especially in the billing system, which has disrupted service delivery. This study aimed to analyze and assess the readiness of outpatient unit staff at Hospital X in implementing EMRs. The study used a quantitative descriptive approach, collecting data through questionnaires that assessed perceived usefulness, perceived ease of use, staff readiness, and attitudes toward EMRs. The population included 23 outpatient unit staff members actively using the EMR system, comprising 4 registration officers, 10 polyclinic nurses, and 9 pharmacists. Total sampling was employed, and responses were measured using a Likert scale to determine the level of agreement with various statements. The results showed that 19 officers were categorized as